Genetics of Parkinson S Disease: Dominant Forms and Gba; [Genética en la Enfermedad de Parkinson: Formas Dominantes y Gba] - Chana-Cuevas, P (Spanish Society of Neurology, 2024)
Parkinson s disease (PD) accounts for a significant burden on modern society, with an increasingly rapid growth in cases. Variants of several genes have been linked to the risk of developing the disease (e.g., the GBA gene). Other genes have been associated with autosomal dominant (e.g., SNCA, LRRK2, VPS35) and autosomal recessive PD (e.g., PRKN, PINK1, DJ-1). Such genes as 13A2, FBXO7, PLA2G6, SYNJ1, and DNAJC6 are associated with recessive forms displaying early onset, greater severity, and atypical characteristics. The genetic study of PD has clinical implications, shedding light on the underlying molecular mechanisms and potential therapeutic targets. This article presents a brief review of the molecular and genetic mechanisms and the phenotype–genotype relationship of GBA and other genes associated with autosomal dominant monogenic PD. © 2024